Physical activity and the drive to exercise in anorexia nervosa. Issue 1 (5th September 2014) - Keyes, Alexandra; Woerwag‐Mehta, Sabine; Bartholdy, Savani; Koskina, Antonia; Middleton, Benita; Connan, Frances; Webster, Peter; Schmidt, Ulrike; Campbell, Iain C.
ABSTRACT Objectives To investigate physical activity (PA) and drive for exercise in anorexia nervosa (AN) in relation to eating disorder (ED) pathology and anxiety. Method Female participants were recruited into four groups: AN outpatients (n = 37), AN inpatients (n = 18), an anxiety group (n = 34), and healthy controls (HCs; n = 30). PA was measured by actigraphy and self‐report together with drive/reasons for exercise, ED pathology, anxiety, depression, stress, BMI, and body composition. Results ED psychopathology, general psychopathology, and physiological measures were consistent with diagnosis. All groups showed a wide range in activity, especially on self‐report. No significant group differences were observed in objective PA levels, yet AN groups reported 57–92% higher total activity than HCs. Outpatients reported more walking and moderate exercise than HCs, and inpatients reported more walking but less moderate and vigorous activity than all other groups. AN groups had significantly higher drive to exercise and valued "improving tone" as important and health and enjoyment as less important reasons to exercise. Discussion Self‐perceived activity rather than objective data may partly explain the increased activity reported in AN. Drive to exercise in AN appears to be more related to ED pathology than to anxiety. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:46–54)